2008
DOI: 10.1002/dvg.20417
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages in the embryo and beyond: Much more than just giant phagocytes

Abstract: Originally recognized as an essential part of the innate and acquired immune systems, macrophages emerged as omnipresent and influential regulators of embryo- and organo-genesis, as well as of tissue and tumor growth. Macrophages are present essentially in all tissues, beginning with embryonic development and, in addition to their role in host defense and in the clearance of apoptotic cells, are being increasingly recognized for their trophic function and role in regeneration. Some tissue macrophages are also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
95
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 176 publications
(189 reference statements)
2
95
0
Order By: Relevance
“…In turn TAMs secrete cytokines and growth factors (e.g., MMP-1, CXCL12) which stimulate tumor cells with the potential to become circulating tumor cells (CTCs) (2)(3)(4). TAMs and CTCs then migrate via the lymphatic system or intravasate across intratumor capillary barriers into peripheral circulation (4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…In turn TAMs secrete cytokines and growth factors (e.g., MMP-1, CXCL12) which stimulate tumor cells with the potential to become circulating tumor cells (CTCs) (2)(3)(4). TAMs and CTCs then migrate via the lymphatic system or intravasate across intratumor capillary barriers into peripheral circulation (4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Although their role in host defense has been well documented, macrophages and their precursors are also important during embryogenesis, normal tissue maintenance, and postnatal organ repair. 1,2 Almost all developing organs contain a population of resident monocytes that infiltrate very early during organogenesis and persist throughout adult life. [3][4][5][6] In addition to their phagocytic capabilities during tissue remodeling-associated apoptosis, 5,7 fetal macrophages have many trophic effects that promote tissue and organ growth.…”
mentioning
confidence: 99%
“…3 Embryonic macrophages appear to play a positive trophic role that may have parallel reparative functions in many adult tissues undergoing repair and cellular replacement. 1,20 A number of studies have suggested that infiltrating macrophages along with the trophic factors they release participate in tissue repair of the kidney, 20 -22 brain, 23 skin, 24,25 lung, 26 liver, 27 heart, 28 gastrointestinal tract, 29,30 and skeletal muscle. 31,32 Indeed, the pleiotrophic roles for CSF-1 in reproduction, development of multiple organ systems, and maternal-fetal interactions during pregnancy by macrophage-mediated processes have also been well defined.…”
mentioning
confidence: 99%
“…Macrophages are a type of white blood cell that are commonly associated with these reactions [93,94]. Macrophages are found in all tissues [95], and are known to secrete reactive oxygen species (ROS) which have been found to increase the corrosion of other metallic biomaterials such as Ti [96].…”
Section: Macrophagesmentioning
confidence: 99%